A case report of true prehallux. (June 2015) - Okumoto, Takayuki; Aramaki-Hattori, Noriko; Taguchi, Yoshihiro; Inoue, Yoshikazu; Matsuzaki, Kyoichi; Kishi, Kazuo
Abstract: Preaxial prehallux is a rare clinical manifestation among patients with polydactyly. Few cases arising from tarsal bones have been reported. We present a case of a true prehallux occurring in a patient with a bilateral complete cleft lip, palate, and alveolus.